2003
DOI: 10.1111/j.1745-4522.2003.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles of Goat Milk and Domiati Cheese as Affected by Pasture Feeding and Stage of Lactation

Abstract: Twenty lactating Alpine goats were randomly allocated into four groups to investigate the efect offeeding regimes with concentrates on fatty acid profiles of goat milk and Domiati cheese at diferent stages of lactation. Pooled milkfiom each group was collected twice monthly for Domiati cheese making. Cheese was sampled Pesh and at 1 and 2 months of pickling in whey. Caproic, caprilic and capric acids in goat milk were recorded at 1.9, 5.5 and 25.1 ,ug/g of fat, respectively, and accounted for 13.27% of total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The percentage of total unsaturated FFA in total FFA of cheese was 26.56%. Similarly, Soryal et al (2003) reported that total unsaturated fatty acids represented 26.83% of total fatty acids in goat milk. Short-chain FFA accounted for only 3.00% of the total FFA.…”
Section: Ffa Profile Of Cheesesmentioning
confidence: 92%
“…The percentage of total unsaturated FFA in total FFA of cheese was 26.56%. Similarly, Soryal et al (2003) reported that total unsaturated fatty acids represented 26.83% of total fatty acids in goat milk. Short-chain FFA accounted for only 3.00% of the total FFA.…”
Section: Ffa Profile Of Cheesesmentioning
confidence: 92%
“…Flavor is highly affected from the profile and concentration of free fatty acids in cheese. There are a limited number of researches on enlightening the effect of fatty acid profile and concentration on quality characteristics of goat milk cheeses (Martin-Hernandez and Juarez, 1992;Attaie and Richter, 1996;Soryal et al, 2003). In fresh cheeses, overall acceptability was determined to be 7.25 in cheese group produced from raw milk while it was determined to be 6.50 in cheese group produced from heat treated milk.…”
Section: Sensory Propertiesmentioning
confidence: 99%
“…The specific smell of goat milk is related primarily to the composition of the fatty acids (Chilliard et al, 2003). The content of caproic (C 6:0 ), caprylic (C 8:0 ), and capric (C 10:0 ) acids in goat milk are slightly higher than that of cow milk (Barber et al, 1997;Chilliard et al, 2000), and these acids compose 13.3% of the total fatty acids in goat milk (Soryal et al, 2003). During fermentation, goat milk will lose its "goaty" smell and the nutritive value of goat milk can increase (Slacacac et al, 2010).…”
Section: Introductionmentioning
confidence: 99%